An Investigation into Lixical Transferring in the Translation of Business Contrancts from English into Vietnamese a Translational Perspective - Phạm Thị Hoàng Yến (2011)
"First of all, I would like to express my gratitude to my respected supervisor, Tran Dinh Nguyen,M.A., for his invaluable guidance and support to my research.I wish to thank the …"